The Positive Impact of Auditory Intellectually Repetition Learning Model Assisted by Domino Card on Mathematics Learning Outcomes - Adiani, Ni Putu; Rini Kristiantari, Maria Goreti (Universitas Pendidikan Ganesha, 2020)
This research-based on problems in students learning outcomes is still low because students are still difficult in understanding mathematics formulas and consider mathematics as difficult learning. This research aimed to know the effect of the Auditory Intellectually Repetition learning model assisted by domino card results on student mathematics learning outcomes grade IV Research design used a nonequivalent control group. The population was 9 groups which amounts to 338 students. Sampling used cluster random sampling technique when chosen experimental group total of 35 students and control group total of 40 students. Objective test type multiple choice used as data collection instruments. Data obtained was data on learning outcomes in mathematics in the cognitive realm and analyzed used uji-t by formula polled variance, analysis result obtained was tcount=3,818 > ttable =1,666, this showed Auditory Intellectually Repetition learning model-assisted domino card give effect to student mathematics learning outcomes. So with the enactment of this model can simplify the way students learn in understanding mathematic formulas.